Efeitos da radiação uv, temperatura e vapor aquecido nos compósitos poliméricos: monitoramento, instabilidade estrutural e fratura - Felipe, Raimundo Nonato Barbosa (2012)
The application of composite materials and in particular the fiber-reinforced plastics (FRP) has gradually conquered space from the so called conventional materials. However, challenges have arisen when their application occurs in equipment and mechanical structures which will be exposed to harsh environmental conditions, especially when there is the influence of environmental degradation due to temperature, UV radiation and moisture in the mechanical performance of these structures, causing irreversible structural damage such as loss of dimensional stability, interfacial degradation, loss of mass, loss of structural properties and changes in the damage mechanism. In this context, the objective of this thesis is the development of a process for monitoring and modeling structural degradation, and the study of the physical and mechanical properties in FRP when in the presence of adverse environmental conditions (ageing). The mechanism of ageing is characterized by controlled environmental conditions of heated steam and ultraviolet radiation. For the research, it was necessary to develop three polymer composites. The first was a lamina of polyester resin reinforced with a short glass-E fiber mat (representing the layer exposed to ageing), and the other two were laminates, both of seven layers of reinforcement, one being made up only of short fibers of glass-E, and the other a hybrid type reinforced with fibers of glass-E/ fibers of curaua. It should be noted that the two laminates have the lamina of short glass-E fibers as a layer of the ageing process incidence. The specimens were removed from the composites mentioned and submitted to environmental ageing accelerated by an ageing chamber. To study the monitoring and modeling of degradation, the ageing cycles to which the lamina was exposed were: alternating cycles of UV radiation and heated steam, a cycle only of UV radiation and a cycle only of heated steam, for a period defined by norm. The laminates have already undergone only the alternating cycle of UV and heated steam. At the end of the exposure period the specimens were subjected to a structural stability assessment by means of the developed measurement of thickness variation technique (MTVT) and the measurement of mass variation technique (MMVT). Then they were subjected to the mechanical tests of uniaxial tension for the lamina and all the laminates, besides the bending test on three points for the laminates. This study was followed by characterization of the fracture and the surface degradation. Finally, a model was developed for the composites called Ageing Zone Diagram (AZD) for monitoring and predicting the tensile strength after the ageing processes. From the results it was observed that the process of degradation occurs Abstract Raimundo Nonato Barbosa Felipe xiv differently for each composite studied, although all were affected in certain way and that the most aggressive ageing process was that of UV radiation, and that the hybrid laminated fibers of glass-E/curaua composite was most affected in its mechanical properties